2019
DOI: 10.1021/acs.jcim.8b00931
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Characterization of Structural Distinctions between Isoforms of Human and Mouse Sphingosine Kinases for Accelerating Drug Discovery

Abstract: Alterations in cellular signaling pathways are associated with multiple disease states including cancers and fibrosis. Current research efforts to attenuate cancers, specifically lymphatic cancer, focus on inhibition of two sphingosine kinase isoforms, sphingosine kinase 1(SphK1) and sphingosine kinase 2 (SphK2). Determining differences in structural and physicochemical binding site properties of SphKs is attractive to refine inhibitor potency and isoform selectivity. This study utilizes a predictive in silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
(145 reference statements)
0
15
0
Order By: Relevance
“…Molecular modeling studies conducted with similar SphK inhibitors possessing a guanidine head group predict that the guanidine moiety in our scaffold hydrogen-bonds to catalytic amino acid residue Asp211, flanking the ATP active site when docked in the Sph binding pocket of SphK2. 32,33 Structure−activity relationship (SAR) studies conducted by Congdon et al on the scaffold of 7 established that deletion of the aryl portion of the octylbenzene tail resulted in a significantly diminished inhibition toward SphK2, demonstrating that the aryl ring is essential for inhibitor efficacy. 21 Further SAR experiments focused on the tail portion led to the development of inhibitors 8 and 9 (SLM6031422) (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular modeling studies conducted with similar SphK inhibitors possessing a guanidine head group predict that the guanidine moiety in our scaffold hydrogen-bonds to catalytic amino acid residue Asp211, flanking the ATP active site when docked in the Sph binding pocket of SphK2. 32,33 Structure−activity relationship (SAR) studies conducted by Congdon et al on the scaffold of 7 established that deletion of the aryl portion of the octylbenzene tail resulted in a significantly diminished inhibition toward SphK2, demonstrating that the aryl ring is essential for inhibitor efficacy. 21 Further SAR experiments focused on the tail portion led to the development of inhibitors 8 and 9 (SLM6031422) (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Sph binding site of SphKs can be divided up into three regions, as defined by Worrell et al They are as follows: (1) the head region adjacent to the ATP binding site, (2) the hydrophobic core region, and (3) the tail region. 33 Molecular docking of 8 and 9 demonstrate different ligand orientations in the Sph binding site of SphK2, giving insight into the role and influence the trifluoromethyl group has in regard to SphK2 selectivity (Figure 4). Compound 8 docks in the Sph binding pocket of SphK2 in a position that indicates more interactions in the tail region of the binding site, as influenced by the hydrophobic core of the pocket, in particular, the space for the trifluoromethyl group to sit between hydrophobic residues Phe548, Leu544, and Leu547 (Figure 4A,B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The open pedagogy design approach to UR in biochemistry and utilization of computational techniques reinforces wet‐lab experiences and have been successful in creating meaningful poster presentations and publications. In using this approach, to date, we have supported UR students to present in over 40 poster sessions at 10 different local, national, and international conferences and be authors on 5 peer‐reviewed research articles in notable journals 5–9 . This short communication highlights an open pedagogy design approach to UR in biochemistry and the utilization of computational techniques and tools to both reinforce wet‐lab experiences and provide routes for experiential learning and workforce development when in‐person laboratory work is not feasible.…”
Section: Figurementioning
confidence: 99%
“…Therefore, we introduced BODIPY, which generally shows a fluorescence value of 500 nm, into PF-543. Extensive docking studies of SK1 in several laboratories have demonstrated that a structurally bulky group can be docked at the tail of SK1 inhibitors [21]. Therefore, we hypothesized that the bulky structure of BODIPY does not significantly affect its SK inhibitory effect.…”
Section: Introductionmentioning
confidence: 96%